(3GdeUHGM GdefjQ aj ZQjH GdTQM GdcHjQs - (3CMeO Hf eMeO Hf Ydj Gdajhej GdMehj, CHh GdYHGS,J (B770 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Gdajhei GdebQi YaG Gddg Yfg (B: (3GdMeO ddg QH GdYGdejf hHYO aEfi cfJ LeYJ cJGHkG ai ZQjH TQM GdhLjR ddQGaYi s
(3BNQgG (B:s
(3hef cJH GdJaSjQ hGdfMh hOhGhjf GdCTYGQ Yf GdCFeI GdeTghQjf GdeCNhP CbhGdge Gdehbha YfO fUhUge hGQGFge eKd GHf GdCYQGHi hfSCd Gddg MSf GdYGbHI ai GdOfjG hGdCNQI s
(3GdfSNI HgG MhGTs
(3HOGNdgG JUhjHGJ ddeDdas
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B224 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B132s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs